Quality evaluation of the educational systems & educational administration and institutions (Evaluación de calidad de un sistema educativa: aspectos educativos e institucionales) - Pazhakh, A.R. (Facultad de Contaduría Pública y Administración U.A.N.L., 2006)
Abstract. The quality evaluation of educational systems as well as educational administration and institutions are described and discussed. Different analytical and conceptual approaches to these points are given. Conclusions are drawn and future lines of research in these topics are suggested and pointed out. Resumen. La calidad de los sistemas educativas, asi como la administración educative y las instituciones son descritas y discutidas. Se presentan distintos acercamientos analíticos y conceptuales para estos puntos. Se presentan conclusiones y además, se señalan las futuras líneas de investigación en este respecto.